2015
DOI: 10.1051/0004-6361/201526617
|View full text |Cite
|
Sign up to set email alerts
|

Low-metallicity massive single stars with rotation

Abstract: Context. Low-metallicity environments such as the early Universe and compact star-forming dwarf galaxies contain many massive stars. These stars influence their surroundings through intense UV radiation, strong winds and explosive deaths. A good understanding of low-metallicity environments requires a detailed theoretical comprehension of the evolution of their massive stars. Aims. We aim to investigate the role of metallicity and rotation in shaping the evolutionary paths of massive stars and to provide theor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
214
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(220 citation statements)
references
References 148 publications
(200 reference statements)
4
214
1
1
Order By: Relevance
“…The origin of He iiλ1640 emission in galaxies has been a matter of investigation, possibly produced by massive stars both in the local Universe (e.g., Szécsi et al 2015;Gräfener & Vink 2015) and at high-redshift (e.g., Cassata et al 2013;Sobral et al 2015;Pallottini et al 2015). He iiλ1640 detection is generally A51, page 10 of 13 associated with AGN activity, but it has also been reported that He iiλ1640 associated with no C ivλ1550 is a possible feature in star-forming galaxies at z ∼ 3 (Cassata et al 2013).…”
Section: Is Ion2 An Agn?mentioning
confidence: 99%
“…The origin of He iiλ1640 emission in galaxies has been a matter of investigation, possibly produced by massive stars both in the local Universe (e.g., Szécsi et al 2015;Gräfener & Vink 2015) and at high-redshift (e.g., Cassata et al 2013;Sobral et al 2015;Pallottini et al 2015). He iiλ1640 detection is generally A51, page 10 of 13 associated with AGN activity, but it has also been reported that He iiλ1640 associated with no C ivλ1550 is a possible feature in star-forming galaxies at z ∼ 3 (Cassata et al 2013).…”
Section: Is Ion2 An Agn?mentioning
confidence: 99%
“…For example, let us consider the fraction of massive binary systems in which mass transfer starts already during the main sequence evolution of the primary star. This depends on the maximum radius that a star reaches on the main sequence, which depends on a number of rather uncertain processes such as convection and overshooting, (e.g., calibrations by Pols et al 1997;Ribas et al 2000;Brott et al 2011a), further mixing processes such as those induced by rotation (e.g., Yoon & Langer 2005;Brott et al 2011b;Ekström et al 2012;Szécsi et al 2015), mass loss by stellar winds and eruptions (review by Smith 2014), and the possible density inversions in the outer layers of massive stars that can result in inflated envelopes (e.g., Yusof et al 2013;Köhler et al 2015, andJiang et al 2015, submitted). Varying the maximum radius of main sequence stars by 30% up and down and allowing for uncertainties in the initial distributions, we find a large variation for this fraction, 20%-50%.…”
Section: Introductionmentioning
confidence: 99%
“…For instance a homogeneous evolution during the Main-Sequence is obtained at a smaller initial rotation in meridional current models than in shear models. As an illustration of this, the models of [51] (that belong to the family of the meridional current models) show that for a metallicity corresponding to that I Zw 18, i.e. Z= 0.0004, a homogeneous evolution is obtained for a 39 M ⊙ already for an initial rotation equal to 350 km s −1 .…”
Section: Rotationmentioning
confidence: 95%
“…Also the minimum mass of single star entering a Wolf-Rayet stage is decreased by rotation. Many grids of rotating stellar models have appeared in the last decade [4,11,16,20,51]. Although these grids are all presented under the generic name of rotating stellar models, they are computed sometimes with very different physics.…”
Section: Rotationmentioning
confidence: 99%
See 1 more Smart Citation